Areas for Improvement and Barriers Identified in Measuring the Quality of Nursing Care: Perceptions of Patients and Professionals - Maria Consuelo Company-Sancho; Manuel Rich-Ruiz; Marta Guillen Toledano; Luis-Miguel Cairós-Ventura; Josefa D. Gil Perez; Ana María de Pascual y Medina; María Pilar Peláez Alba; Ana Isabel Barreno Estévez; María Emma Alonso Poncelas; Carolina Rodríguez Orihuela; Pedro Ruyman Brito-Brito (Nursing Reports)
Background: Quality indicators in healthcare are essential to raising awareness about the appropriateness of nursing care. However, identifying the key indicators continues to pose a challenge, above all if one wants to include users and professionals. Aim: Identify which aspects of nursing care should be measured to assess the results of nursing care and how to do so. Methodology: Interpretive qualitative exploratory study. The participants were users and professionals of an autonomous regional health service in Spain. The information was collected by means of two focus groups and eight semi-structured interviews conducted between November 2022 and March 2024. The data were analysed thematically using the Braun and Clarke process. Results: The users and professionals agreed on the need to measure emotional skills and attitudes such as empathy, respect, and warmth when dealing with patients. The professionals highlighted workload and inefficiency of the current record system as barriers to adequately reflecting their work. They proposed improvements in the recording tool and the need for more human resources, as well as leadership that is more focused on quality. Conclusions: It is crucial to develop indicators that reflect both the emotional and technical aspects of nursing care. The participation by patients and professionals alike in this design and selection will make it possible to improve the quality of care and advances in the nursing profession. This study was not registered.